Kebaikan yang Menyesatkan: Ketika Utilitarianisme Menjauhkan Manusia dari Allah - Jansen Hutabarat (Majalah Ilmiah METHODA, 2025)
This study discusses the relationship between utilitarianism as a consequentialist ethical theory and the Christian faith, specifically how utilitarianism can give birth to a “perverse goodness” and lead people away from God. Utilitarianism judges morality based on the end result that produces the greatest happiness for the greatest number of people. Although seemingly noble, this approach often justifies morally wrong actions-such as lying, murder, euthanasia, sacrificing the minority for the majority, even war policies-as long as they are deemed to bring greater benefits. The results of the study show that the utilitarianism paradigm has the potential to ignore the dignity of human beings created in the image of God, give rise to moral relativism, and separate goodness from God's will. In the perspective of Christian Moral Theology and Divine Command Theory, goodness is not only measured by social consequences but also by obedience to God's command. Thus, actions that seem good according to utilitarian logic are not necessarily right according to Christian morality, because true goodness must bring people. This study confirms that the “ends justify the means” logic of utilitarianism contradicts the absolute divine moral principle. Believers are called to be wary of the pragmatic goodness that leads to deception, and to hold on to the truth of God's word, which is the highest standard of morality. Thus, this study contributes to the understanding of Christian ethics in facing modern moral challenges that are often wrapped in the pretext of public benefit.